Are multitasking abilities impaired in welders exposed to manganese? Translating cognitive neuroscience to neurotoxicology - van Thriel, Christoph; Quetscher, Clara; Pesch, Beate; Lotz, Anne; Lehnert, Martin; Casjens, Swaantje; Weiss, Tobias; Van Gelder, Rainer; Plitzke, Katrin; Brüning, Thomas; Beste, Christian; WELDOX II Study Group (Archives of toxicology, 2017)
Manganese (Mn) is an essential trace element with well characterized neurotoxic effects in high concentrations. Neurochemically, the initial neurotoxic effect of Mn is the perturbation of striatal γ-aminobutyric acid levels. Specific tasks for the assessment of cognitive functions subserved by fronto-striatal loops are available as the stop-change task (SCT) assessing control of multi-component behavior and action cascading. In a cross-sectional study, fifty male welders and 28 age-matched controls completed the SCT during a whole day examination. Reaction times, responses accuracy, and event-related potentials (ERPs) from electroencephalogram (EEG) recordings were analyzed. The shift exposure of the welders to respirable Mn was stratified by 20 µg/m3 in 23 low-exposed (median = 4.7 µg/m3) and 27 high-exposed welders (median = 86.0 µg/m3). Welders graduation was lower and was therefore included in the analyses. The task-related factor (stop-change delay, SCD) modified the responses as expected; however, the lack of an interaction "SCD × group" revealed no differences between welders and controls. EEG data showed that the "SCD" modulated the amplitude of the P3 ERP in controls stronger than in welders. There was no difference between the two groups of welders and no association between airborne or systemic Mn and the P3 ERP. Moreover, the P3 amplitude was smaller in subjects with lower education. These results showed that multitasking performance and cognitive flexibility are not impaired in welders. The electrophysiological results gave a weak hint that relevant neurobiological processes were different in welders as compared to controls but this may be related to lower education.
Keywords: reakční čas; Cross-Sectional Studies; Electroencephalography; Male; Middle Aged; Occupational Exposure; Welding; Electrophysiology; látky znečišťující vzduch v pracovním prostředí; Toxicity; elektroencefalografie; pracovní expozice; Manganese; Case-Control Studies; Reaction Time; mužské pohlaví; kognitivní neurověda; Neuropsychological Tests; kognice; lidé; studie případů a kontrol; Cognitive Neuroscience; Humans; průřezové studie; Air Pollutants, Occupational; neuropsychologické testy; mangan; Neurobehavioral testing; svařování; lidé středního věku; Cognitive functions; Cognition